Pemenuhan Aspek Kepastian, Kemanfaatan, dan Keadilan Hukum dalam Sengketa Waris - Yusuf HR, Mohammad; Anam, Choirul (Universitas Negeri Malang, 2021)
This study aimed to describe inheritance disputes and the fulfillment of aspects of certainty, utility, and legal justice in the District Court Decision Number 203/Pdt.G/2001/PN.Mlg and the Supreme Court Decision Number 2332K/Pdt/2003. This study used a normative legal method by conceptualizing a statutory regulation. This study was a qualitative descriptive study because it aimed to describe the Decision of the District Court Number 203/Pdt.G/2001/PN.Mlg and the Decision of the Supreme Court Number 2332K/Pdt/2003 systematically and accurately. Inheritance disputes in the District Court Decision Number 203/Pdt.G/2001/PN.Mlg and the Supreme Court Decision Number 2332K/Pdt/2003 were acts that aimed at controlling the inheritance without the knowledge of the heirs. The decision of the District Court Number 203/Pdt.G/2001/PN.Mlg did not reflect the aspects of certainty, utility, and legal justice. It did not pay attention to and considered Law Number 1 of 1974, the provisions of Article 118 paragraph (1) Herzien Inlandsch Reglement, and evidence from the defendants. The Supreme Court’s decision Number 2332K/Pdt/2003 reflected the aspects of certainty, benefit, and legal justice because it has taken into account and considered the facts and evidence in the trial in the form of a certificate from the inheritance hall as well as a copy of the Decree of the Religious Court Number 4026/1985.